Dementia Approach and Follow-up in Primary Care - Ana Jorge Oliveira Lopes; Vitor Martins; João Ribeiro (Instituto Politécnico de Viseu, 2017)
Introduction: The prevalence of dementia has been increasing in recent years in parallel with an ageing population. Today it is a common pathology in primary care level. Objectives: To review the family physician's role in diagnosing and following up on patients with dementia. Methods: Theoretical review based on researching clinical guidelines, systematic and original articles published in English and Portuguese in PubMed, Clinical Key, UpToDate, the Index of Portuguese Journals from January 2006 to September 2016 using the MeSH terms: "Dementia," "Primary Health Care," "Primary Care Nursing" and "Primary Care Physician." Results: When dementia is suspected, it is important to resort to family members and/or caregivers' cooperation, to conduct a thorough medical history of the patient, focusing on behavioural and cognitive symptoms and changes in daily activities. Subsequently, an objective examination should be carried out and an array of cognitive, psycho-affective and functional assessment tests applied. Finally, an analytical and imaging evaluation should be performed. Equally important is the role of the family physician in the patient's subsequent treatment/guidance and support to families and caregivers in care management. Conclusions: The family physician is in a prime position for early detection of dementia. Clinical diagnosis is essential and is not always easy at an early stage. The role of doctors and other professionals in primary health care should not be limited to the initial assessment, but should extend to following up on and guiding the sick and their respective families.